The Role of Sanitarian and Social-Cultural Factors in Promoting the Open Defecation-Free (ODF) Village - Anisa Haq Elhanur; Putri Nabilah Ramadhani; R Azizah (JURNAL KESEHATAN LINGKUNGAN, 2021)
Introduction: Open defecation behavior can be a means of spreading disease. A person's defecation behavior can be influenced by supporting factors provided by health workers, the socio-cultural environment and access to healthy latrine facilities. The aim of this study was to analyze the role of families, community leaders, health workers and the socio-cultural environment on defecating behavior in ODF and non-ODF villages. Methods: This study used quantitative and qualitative observational analytic. The study design was cross sectional design. All people who live on the banks of railway in non ODF and ODF villages were the population in this study. A total of 68 peoples were sampled who determined by themethod proportional random sampling. The independent variables were family support, sanitarian support, community leaders support, the health department team support, socio-culture and population density. The dependent variable was defecation activity. Data were collected by field observation and questionnaires. The collected data were analyzed using the Mann Whitney Test. Results and Discussion: There was no difference in family support (p = 0.661), community leaders support (p = 0.122), the health department team support (p = 0.555). However, there were differences in sanitarian officers support (p = 0.000), the socio-cultural environment (p = 0.000) and the population density in non ODF villages is higher than in ODF villages. Conclusion: There were differences in sanitarian officers support, the socio-cultural environment and population density between non ODF and ODF villages.